The Oxford handbook of business and the natural environment - Bansal, Pratima.; Hoffman, Andrew J., 1961- (Oxford handbooks in business and management., 2012)
This handbook discusses the main issues, research, and theory on business and the natural environment, and how they impact on different business functions and disciplines.